Aversive Learning of Colored Lights in Walking Honeybees - Kirkerud, Nicholas H.; Schlegel, Ulrike; Giovanni Galizia, C. (Frontiers in Behavioral Neuroscience, 2017)
The honeybee has been established as an important model organism in studies on visual learning. So far the emphasis has been on appetitive conditioning, simulating floral discrimination and homing behavior, where bees perform exceptionally well in visual discrimination tasks. However, bees in the wild also face dangers, and recent findings suggest that what is learned about visual percepts is highly context dependent. A stimulus that follows an unpleasant period, is associated with the feeling of relief- or safety in humans and animals, thus acquiring a positive meaning. Whether this is also the case in honeybees is still an open question. Here, we conditioned bees aversively in a walking arena where each half was illuminated by light of a specific wavelength and intensity, one of which was combined with electric shocks. In this paradigm, the bees’ preferences to the different lights were modified through nine conditioning trials, forming robust escape and avoidance behaviors. Strikingly, we found that while 465nm (human blue) and 590nm (human yellow) lights both could acquire negative valences (inducing avoidance response), 525nm (human green) light could not. This indicates that green light holds an innate meaning of safety which is difficult to overrule even through intensive aversive conditioning. The bees had slight initial preferences to green over the blue and the yellow lights, which could be compensated by adjusting light intensity. However, this initial bias played a minor role while the chromatic properties were the most salient characteristics of the light stimuli during aversive conditioning. Moreover, bees could learn the light signaling safety, revealing the existence of a relief component in aversive operant conditioning, similar to what has been observed in other animals.